Studies on the Role of the Transcription Factor Tcf21 in the Transdifferentiation of Parietal Epithelial Cells into Podocyte-Like Cells. - Kliewe, Felix; Kuss, Andreas W.; Siegerist, Florian; Schröder, Sindy; Schordan, Sandra; Artelt, Nadine; Kindt, Frances; Amann, Kerstin Ute; Lindenmeyer, Maja T.; Endlich, Karlhans; Endlich, Nicole (Cellular Physiology and Biochemistry, 2021)
BACKGROUND/AIMS: Podocyte differentiation is essential for proper blood filtration in the kidney. It is well known that transcription factors play an essential role to maintain the differentiation of podocytes. The present study is focused on the basic helix-loop-helix (bHLH) transcription factor Tcf21 (Pod1) which is essential for the development of podocytes in vivo. Since parietal epithelial cells (PECs) are still under debate to be progenitor cells which can differentiate into podocytes, we wanted to find out whether the expression of Tcf21 induces a transition of PECs into podocytes. METHODS: We transfected PECs with Tcf21-GFP and analyzed the expression of PEC- and podocyte-specific markers. Furthermore, we performed ChIP-Seq analysis to identify new putative interaction partners and target genes of Tcf21. RESULTS: By gene arrays analysis, we found that podocytes express high levels of Tcf21 in vivo in contrast to cultured podocytes and parietal epithelial cells (PECs) in vitro. After the expression of Tcf21 in PECs, we observed a downregulation of specific PEC markers like caveolin‑1, β-catenin and Pax2. Additionally, we found that the upregulation of Tcf21 induced multi-lobulation of cell nuclei, budding and a formation of micronuclei (MBM). Furthermore, a high number of PECs showed a tetraploid set of chromosomes. By qRT-PCR and Western blot analysis, we revealed that the transcription factor YY1 is downregulated by Tcf21. Interestingly, co-expression of YY1 and Tcf21 rescues MBM and reduced tetraploidy. By ChIP-Seq analysis, we identified a genome-wide Tcf21-binding site (CAGCTG), which matched the CANNTG sequence, a common E-box binding motif used by bHLH transcription factors. Using this technique, we identified additional Tcf21 targets genes that are involved in the regulation of the cell cycle (e.g. Mdm2, Cdc45, Cyclin D1, Cyclin D2), on the stability of microtubules (e.g. Mapt) as well as chromosome segregation. CONCLUSION: Taken together, we demonstrate that Tcf21 inhibits the expression of PEC-specific markers and of the transcription factor YY1, induces MBM as well as regulates the cell cycle suggesting that Tcf21 might be important for PEC differentiation into podocyte-like cells.
EVALuna2:466165